1997
DOI: 10.1177/135910539700200215
|View full text |Cite
|
Sign up to set email alerts
|

Modality of Communication and Recall of Health-related Information

Abstract: A health warning was presented to 89 female and 19 male students aged 17-36 years via three modalities or channels of communication: a "talking head" (video), an audiotape recording (audio), or a printed transcript (print). The verbal content of the message was identical in all three conditions. Participants' free recall, cued recall (recognition), and global recall of the message was then measured. On two separate dependent measures and a combined measure, recall was significantly (p < .005) better in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
1
35
2
Order By: Relevance
“…For instance, visual cues like the appearance and the non-verbal behavior of a spokesperson can distract from what the spokesperson is saying. When recipients are distracted, processing of the message is likely impaired which can result in decreased effectiveness (Corston & Colman, 1997). On the other hand, it is possible that the audiovisual modality can initially attract viewers' attention to the message and enhance processing (Taylor & Thompson, 1982).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, visual cues like the appearance and the non-verbal behavior of a spokesperson can distract from what the spokesperson is saying. When recipients are distracted, processing of the message is likely impaired which can result in decreased effectiveness (Corston & Colman, 1997). On the other hand, it is possible that the audiovisual modality can initially attract viewers' attention to the message and enhance processing (Taylor & Thompson, 1982).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers have suggested that video is more distracting than print, because features of the presentation can draw attention away from the content of the message (Byrne & Curtis, 2000;Corston & Colman, 1997). For instance, visual cues like the appearance and the non-verbal behavior of a spokesperson can distract from what the spokesperson is saying.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaiken and Eagly (1983) and other researchers in communications and media studies (Byrne & Curtis, 2000;Corston & Colman, 1997;Green, 1981;Potter & Choi, 2006) have continued to investigate the audio modality effect in advertisements and other messages, as well as the impact of content and structural complexity on recall. Valkenburg and Beentkes (1997) explored memory retention among young students, positing the supposed superiority of audio information for creative visualization, and thus 'faulty memory', but finding that successful recall had more to do with the age of their subjects, rather than modality.…”
Section: Introductionmentioning
confidence: 99%